2012
DOI: 10.1051/0004-6361/201219834
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric extinction properties above Mauna Kea from the Nearby SuperNova Factory spectro-photometric data set

Abstract: We present a new atmospheric extinction curve for Mauna Kea spanning 3200-9700 Å. It is the most comprehensive to date, being based on some 4285 standard star spectra obtained on 478 nights spread over a period of 7 years obtained by the Nearby SuperNova Factory using the SuperNova Integral Field Spectrograph. This mean curve and its dispersion can be used as an aid in calibrating spectroscopic or imaging data from Mauna Kea, and in estimating the calibration uncertainty associated with the use of a mean extin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 45 publications
2
94
0
Order By: Relevance
“…The redshift z ≈ 0.091 was estimated from a weak narrow unresolved Hα emission, which seems to originate from the SN host galaxy. A line at λ ≈ 4675Å coincides with the HalfPower Point (HPP) between the red and the blue SNIFS channels (Buton et al 2013) redshifted to the iPTF13beo host redshift and shown in Figure 4. Therefore this line is probably an artifact produced by noise at the edges of the SNIFS channels.…”
Section: Spectroscopymentioning
confidence: 98%
See 1 more Smart Citation
“…The redshift z ≈ 0.091 was estimated from a weak narrow unresolved Hα emission, which seems to originate from the SN host galaxy. A line at λ ≈ 4675Å coincides with the HalfPower Point (HPP) between the red and the blue SNIFS channels (Buton et al 2013) redshifted to the iPTF13beo host redshift and shown in Figure 4. Therefore this line is probably an artifact produced by noise at the edges of the SNIFS channels.…”
Section: Spectroscopymentioning
confidence: 98%
“…The first one, referred to here as the 'early spectrum', was taken on 2013 May 21.594, ∼2.2 days after the first SN detection, ∼2.4 days after the estimated SN explosion date (phase: +2.4 days 3 ) and ∼0.3 days before the primary peak. The spectrum was obtained using the Supernova Integral Field Spectrogaph (SNIFS, Lantz et al 2004;Buton et al 2013) mounted on the University of Hawaii 2.2-meter telescope (88-inch, UH88).…”
Section: Spectroscopymentioning
confidence: 99%
“…The pipeline detailed in Bacon et al (2001) performs dark, bias, and flat-field corrections, cleans the data of bad pixels and cosmic rays, then fits and extracts the integral field unit spaxels into a one-dimensional spectrum. The Gaidos et al (2014) reduction takes this spectrum and performs flux calibration and telluric correction based on white dwarf standards taken throughout the night and a model of the atmosphere above Maunakea (Buton et al 2013). The final reduced spectrum of LSPMJ1314+1320AB has a signal-tonoise ratio (S/N) of >100 pixel −1 redward of 6000 Å.…”
Section: Uh22 M/supernova Integral Field Spectrograph (Snifs) and Imentioning
confidence: 99%
“…The flux calibration was developed in Sect. 2.2 of Pereira et al (2013), based on the atmospheric extinction derived in Buton et al (2013). The SNIFS data used in this paper are reduced according to the initial steps of SNIFS pipeline, e.g.…”
Section: Snifsmentioning
confidence: 99%
“…The advantage in calibrating SNIFS with such precision is that it is an integral field spectrograph (IFS), thus allowing us to produce spectrophotometric calibrated spectra of standard stars. These spectra are also corrected for the atmospheric extinction which is computed nightly from standard stars observations (Buton et al 2013). Therefore, the resulting physical calibration can be directly transferred to standard stars.…”
Section: Introductionmentioning
confidence: 99%